Independent Associations of Tumor Necrosis Factor-Alpha and Interleukin-1 Beta With Radiographic Emphysema in People Living With HIV - Thudium, Rebekka F.; Ringheim, Hedda; Ronit, Andreas; Hoel, Hedda; Benfield, Thomas; Mocroft, Amanda; Gerstoft, Jan; Trøseid, Marius; Borges, Álvaro H.; Ostrowski, Sisse R.; Vestbo, Jørgen; Nielsen, Susanne D. (Frontiers in Immunology, 2021)
Background: People living with HIV (PLWH) have increased systemic inflammation, and inflammation has been suggested to contribute to the pathogenesis of emphysema. We investigated whether elevated cytokine concentrations (interleukin (IL)-1β, IL-1 receptor antagonist (IL-1RA), IL-2, IL-4, IL-6, IL-10, IL-17A, tumor necrosis factor-alpha (TNFα), interferon-gamma (IFNγ), soluble CD14 (sCD14) and sCD163 were independently associated with radiographic emphysema in PLWH. Materials and Methods: We included PLWH from the Copenhagen Comorbidity in HIV Infection (COCOMO) Study without hepatitis B and C co-infection and with a plasma sample and a chest computed tomography scan available. Emphysema plus trace emphysema was defined as the percentage of low attenuation area under 950 Hounsfield units (%LAA-950) using a cut-off at 5%. Cytokine concentrations were measured by ELISA or Luminex immunoassays. An elevated cytokine concentration was defined as above the 75th percentile. Results: Of 783 PLWH, 147 (18.8%) had emphysema. PLWH were predominantly male (86.0%) and 743 (94.9%) had undetectable viral replication. PLWH with emphysema had higher concentrations of TNFα (median (IQR): 8.2 (6.4-9.8) versus 7.1 (5.7-8.6) pg/ml, p<0.001), IL-1β (0.21 (0.1-0.4) versus 0.17 (0.1-0.3) pg/ml, p=0.004) and IL-6 (3.6 (2.6-4.9) versus 3.1 (2.0-4.3) pg/ml, p=0.023) than PLWH without. In a logistic regression model adjusted for age, sex, ethnicity, smoking status, BMI and CD4 nadir, elevated TNFα (adjusted odds ratio (aOR): 1.78 [95%CI: 1.14-2.76], p=0.011) and IL-1β (aOR: 1.81 [95%CI: 1.16-2.81], p=0.009) were independently associated with emphysema. The association between IL-1β and emphysema was modified by smoking (p-interaction=0.020) with a more pronounced association in never-smokers (aOR: 4.53 [95%CI: 2.05-9.98], p<0.001). Conclusion: Two markers of systemic inflammation, TNFα and IL-1β, were independently associated with emphysema in PLWH and may contribute to the pathogenesis of emphysema. Importantly, the effect of IL-1β seems to be mediated through pathways that are independent of excessive smoking.